History taught and gender: socio-demographic variables, educational level and curricular itinerary in the Secondary Education students - Ortega-Sánchez, Delfín; Olmos Vila, Rafael (Clio. History and History Teaching, 2019)
The present study seeks to analyze the potential influence of traditional sociodemographic variables (sex, age and geographical origin), and the course and specialty (Science / Humanities and Social Sciences) of a group of Spanish Secondary Education students (n = 124) in their beliefs epistemological and methodological about History and, in particular, in the place given to the social experience of women in the history taught. A quantitative cross-sectional prospective methodology is used, by performing descriptive and inferential statistical analyzes. The results obtained report the absence of statistically significant differences between sex, age, course and specialty in the beliefs, and its existence between the geographical origin of the students and their conceptions on the construction of historical knowledge, and the responsibility of History in the visibility of traditionally invisible people and social and historical groups.
Keywords: historical-social thought; epistemological and methodological beliefs; Gender